The role of digital herbarium collections in the taxonomic revision of complex plant families: Salicaceae sensu stricto - Belyaeva Irina (EDP Sciences, 2021)
The importance of digitisation and digital resources in botanical research is underlined. Advantages and disadvantages of the use of digital herbaria in taxonomic research in Salicaceae sensu stricto are discussed and some suggestions on possible improvements are made.